Anti-Voice Adaptation Suggests Prototype-Based Coding of Voice Identity - Latinus, Marianne; Belin, Pascal (Frontiers in Psychology, 2011)
We used perceptual aftereffects induced by adaptation with anti-voice stimuli to investigate voice identity representations. Participants learned a set of voices then were tested on a voice identification task with vowel stimuli morphed between identities, after different conditions of adaptation. In Experiment 1, participants chose the identity opposite to the adapting anti-voice significantly more often than the other two identities (e.g., after being adapted to anti-A, they identified the average voice as A). In Experiment 2, participants showed a bias for identities opposite to the adaptor specifically for anti-voice, but not for non anti-voice adaptors. These results are strikingly similar to adaptation aftereffects observed for facial identity. They are compatible with a representation of individual voice identities in a multidimensional perceptual voice space referenced on a voice prototype.